Pengembangan Buku Big Book “Miki Si Gajah Kecil” Sebagai Media Pengenalan Literasi Lingkungan - Indri Wijayani, Ida Ayu; Gede Anadhi, I Made; Komang Sindu Putra, Ida Bagus (Generasi Emas, 2023)
Environmental literacy is important for early childhood development as a cognitive experience of the natural environment. However, the introduction of environmental literacy in urban schools requires environmental literacy learning media. The purpose of the study was to develop an environmental literacy big book with the theme "Miki the Little Elephant". The research uses the R&D research method and the ADDIE development method, namely analyze, design, development, implementation, and evaluation. The data source is children and teachers at Taman Kurnia Kindergarten Denpasar. Data collection by observation, interview, and questionnaire instrument. Analysis with qualitative and quantitative descriptive results from the PAUD material expert test results, namely 3 Kindergarten teachers and 2 media expert lecturers. The research was limited to the validation test due to limited time for field testing. The results showed the value of expert validation score 90.00% very high qualification, the results of learning content expert test score 91.67% very high qualification, the results of design expert test score 85.00% high qualification, the results of media expert test score 85.71% high qualification. The conclusion is that the development of big book books as a medium for introducing environmental literacy is very feasible as an early childhood learning media